Duration of the Archive: Soundscapes of Extreme Witnessing in Divya Victor’s Curb - Myk, Małgorzata (Text Matters: A Journal of Literature, Theory and Culture, 2023)
This paper examines the significance of soundscapes in the Tamil American poet Divya Victor’s reconstruction of the archive of anti-South Asian violence in her acclaimed poetry collection Curb (Nightboat Books, 2021). Being a continuation of the poet’s investigation of the limits of conceptual and “documental” poetics (Michael Leong), advanced in her Natural Subjects, UNSUB and Kith, Curb appropriates public and personal records to critique discrimination against the South Asian community in America’s post-9/11 political landscape. Victor’s poetics enact extreme witnessing, re-establishing the archive’s unheard durations that her modality of the lyric upholds, and recovering locutions of the Indian diaspora eroded or erased by anti-immigrant and anti-Asian racism. Tracing the dynamics of location and locution at the sites of violent events as well as their barely audible frequencies registered in the sequence “Frequency (Alka’s Testimony),” I argue that the archive’s duration in Curb is extended by forms of “sonic agency” (Brandon LaBelle). I further show how, through the poetic work of hearing and sounding (including such techniques as echolocation and ventriloquy), Victor creates a simultaneously critical and lyrical space akin to auditory experience where the text’s multiple durational vectors throw into sharp relief the lives “curbed,” diminished, or destroyed by wounding, fear, and trauma, testifying to the extremity of the very act of witnessing. Finally, focusing on opacity as a fundamental quality of the archive, I also turn to Carolyn Chen’s concrète sound compositions and Amarnath Ravva’s assemblages that traverse Curb, accompanying the poet in collaborative hearing of the archive’s spatial, temporal, and sonic dynamics.